Functional and Mechanistic Insights into the Fatty-Acid CoA Ligase FadK in Escherichia coli - Dafeng Liu; Ablikim Abdiriyim; Lvxia Zhang; Feng Yu (Frontiers in Bioscience-Landmark)
Background: Escherichia coli (E. coli) is a common opportunistic bacterial pathogen in both human and animal populations. Fatty acids serve as the central carbon and energy source, a process mediated by fatty acid-coenzyme A (CoA) ligases encoded by fad genes such as FadK. However, the function and the mechanism of FadK remain unclear. Methods: The three-dimensional structure of FadK was modeled using AlphaFold2. After expression and purification, monomeric FadK was successfully isolated. The enzymatic activity was assayed, and real-time quantitative polymerase chain reaction (RT-qPCR) was performed to quantify FadK expression levels. Results: In enzymatic assays of fatty acid CoA ligase activity, caprylic acid was found to be the optimal substrate for FadK. We determined the optimal catalytic conditions for FadK, which include a pH of 7.4, ATP concentration of 0.6 mM, CoA concentration of 0.8 mM, and Mg2+ concentration of 0.8 mM at 37 °C. Notably, the activity of FadK showed a decrease with increasing concentrations of dodecyl-AMP, which was further confirmed by the RT-qPCR results. Conclusions: Our findings will serve as a fundamental framework for the development of innovative therapeutics that target E. coli infections.